First records and a new genus of comb-tailed spiders (Araneae: Hahniidae) from Thailand with comments on the six-eyed species of this family - Rivera-Quiroz, Francisco Andrés; Petcharad, Booppa; Miller, Jeremy A. (European Journal of Taxonomy, 2020)
The family Hahniidae is reported from Thailand for the first time. The genus Hexamatia gen. nov. and two new species, Hexamatia seekhaow gen. et sp. nov. and Hahnia ngai sp. nov., are described and illustrated. DNA sequences are provided for all the species reported here. The phylogenetic position of the novel genus Hexamatia gen. nov. and its relation to Hahnia are discussed. Based on these results, a new combination is proposed for Hexamatia senaria (Zhang, Li & Zheng, 2011) gen. et comb. nov. = Hahnia senaria. Known distribution of the species Hahnia saccata Zhang, Li & Zheng, 2011, originally described from China, is expanded. A brief review and notes on the taxonomy of the six-eyed hahniids are included.